2017
DOI: 10.1038/s41598-017-00534-9
|View full text |Cite
|
Sign up to set email alerts
|

A starvation-induced regulator, RovM, acts as a switch for planktonic/biofilm state transition in Yersinia pseudotuberculosis

Abstract: The transition between the planktonic state and the biofilm-associated state is a key developmental decision for pathogenic bacteria. Biofilm formation by Yersinia pestis is regulated by hmsHFRS genes (β-1, 6-N-acetyl-D-glucosamine synthesis operon) in its flea vector and in vitro. However, the mechanism of biofilm formation in Yersinia pseudotuberculosis remains elusive. In this study, we demonstrate that the LysR-type regulator RovM inversely regulates biofilm formation and motility in Y. pseudotuberculosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…These results suggest that LrhA negatively regulates flhDC expression by directly binding to the flhDC promoter. Consistent with the master regulatory role of FlhD 4 C 2 in flagellar biosynthesis and motility (10,40), there was no motility observed in the ΔflhDC mutant or the ΔlrhA ΔflhDC double mutant ( Fig. 1B).…”
supporting
confidence: 73%
See 1 more Smart Citation
“…These results suggest that LrhA negatively regulates flhDC expression by directly binding to the flhDC promoter. Consistent with the master regulatory role of FlhD 4 C 2 in flagellar biosynthesis and motility (10,40), there was no motility observed in the ΔflhDC mutant or the ΔlrhA ΔflhDC double mutant ( Fig. 1B).…”
supporting
confidence: 73%
“…Therefore, bacteria have evolved a variety of strategies to control the multistep process of cell motility to avoid inappropriate energy expenditure (2,10,57). Previous studies have shown that LrhA and its homologues play a positive or negative role in bacterial motility mainly through controlling the expression of the flagellar master operon flhDC at the transcriptional level (33,35,40). Consistent with the role of LrhA in E. coli but opposite to that in Xenorhabdus nematophila (32,33,35), our results indicate that LrhA in P. alhagi represses flagellar motility by directly inhibiting the transcription of flhDC.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is unlikely as our previous experiments have indicated metabolic, viable activity for cells well into starvation. Biofilm formation is induced by nutrient starvation and inhibited by glucose addition (Thomason, Fontaine, De Lay, & Storz, 2012; Zhao et al, 2017). We therefore reason that glycogen facilitates the attachment phase of biofilm formation under starvation conditions, here by providing resources for matrix protein or flagella production.…”
Section: Resultsmentioning
confidence: 99%
“…Second, transcriptome analyses of CpxR-regulated genes have consistently shown maximal activation of the Cpx pathway in bacteria grown to late stationary phase [11,34,84]. Third, maximal rovM expression in Yersinia occurs at late stationary phase when nutrients needed for growth have been exhausted [56,62,64,65]. Where required, antibiotics were added at the final concentrations of carbenicillin (Cb; 100 μg/ml), kanamycin (Km; 50 μg/ml), Trimethoprim (Tp; 10 μg/ml) and chloramphenicol (Cm; 25 μg/ml).…”
Section: Bacterial Strains Plasmids and Growth Conditionsmentioning
confidence: 99%
“…Control of rovM expression and the CsrA-Crp-RovM-RovA regulatory cascade has clear implications for the lifestyle choices made by Yersinia spp. in terms of planktonic versus sessile growth and survivability in mildly acidic environments or in the flea gut [64][65][66][67].…”
Section: Introductionmentioning
confidence: 99%